Dancing the In-between. The Emergence of Dance from Pathicity, Suspension, and Atmospheric Resonance - Massimo, Serena (Aesthetica Preprint, 2025)
This paper aims to propose a case study of a neo-phenomenological analysis of a contemporary dance work. After presenting the ‘suspended dance’ La Spire, created by Chloe Moglia in 2017, the words used by Moglia herself and the dancers in the choreography will be brought into dialogue with Strausian notions of ‘pathicity’ and ‘tonicity’. They will make it possible to grasp the relevance of the adoption of a ‘pathic’ attitude in the emergence of a dance characterised by multiple constraints. This will be manifested in the analysis of the dancers’ attitude towards gravity, which is far removed from that of everyday life and from that of acrobats. Finally, the neophenomenological notion of the ‘felt body’, the categories linked to it and the concepts of ‘atmospheric affordances’ and ‘atmospheric resonances’ introduced by Tonino Griffero will make it possible to show that the creative dimension of ‘La Spire’ is based on the ability to expose oneself to the affective stimuli present in a way that is not marked by fear of falling but by a spirit of playful complicity.